Effects of Food Label Use on Diet Quality and Glycemic Control Among Latinos With Type 2 Diabetes in a Community Health Worker–Supported Intervention - Kollannoor-Samuel, Grace (Am J Public Health, 2016)
Objectives. To determine the impact of an intervention led by community health workers (CHWs) on food label use and to assess whether food label use and diet quality mediate the intervention’s impact on glycemic control. Methods. From 2006 to 2010, 203 Latinos (intervention group, n = 100; control group, n = 103) in Hartford County, Connecticut, with type 2 diabetes were randomized to an intervention that included 17 CHW-led home-based sessions over a 12-month period in addition to the standard of care available in both study arms. Data on food label use, diet quality, covariates, and glycated hemoglobin (HbA1c) were collected at baseline and at 3, 6, 12, and 18 months. Data were analyzed via mixed effects and multilevel structural equation modeling. Results. Food label use in the intervention (vs control) group was significantly higher at 3, 12, and 18 months (odds ratio = 2.99; 95% confidence interval = 1.69, 5.29). Food label use and diet quality were positive mediators of improved HbA1c levels. Conclusions. Culturally tailored interventions led by CHWs could increase food label use. Also, CHW-delivered food label education may lead to better diet quality and improve glycemic control among Latinos with type 2 diabetes.